2011
DOI: 10.1016/j.ymben.2011.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Mapping photoautotrophic metabolism with isotopically nonstationary 13C flux analysis

Abstract: Understanding in vivo regulation of photoautotrophic metabolism is important for identifying strategies to improve photosynthetic efficiency or re-route carbon fluxes to desirable end products. We have developed an approach to reconstruct comprehensive flux maps of photoautotrophic metabolism by computational analysis of dynamic isotope labeling measurements and have applied it to determine metabolic pathway fluxes in the cyanobacterium Synechocystis sp. PCC6803. Comparison to a theoretically predicted flux ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
364
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(385 citation statements)
references
References 46 publications
(57 reference statements)
19
364
2
Order By: Relevance
“…In the case of the mutant, the activation of PEP carboxylase under photomixotrophic conditions is unlikely due to (1) the low transcript level, (2) low CO 2 fixation activity, and (3) marked accumulation of malate and fumarate, which could inhibit PEP carboxylase activity (Owttrim and Colman, 1986). Metabolic flux analysis performed by Young et al (2011) suggested that PEP carboxylase and malic enzyme cooperate in Synechocystis sp. PCC 6803 (i.e.…”
Section: Effects Of Addition Of Metabolites On the Dcyabrb2 Mutant Unmentioning
confidence: 99%
“…In the case of the mutant, the activation of PEP carboxylase under photomixotrophic conditions is unlikely due to (1) the low transcript level, (2) low CO 2 fixation activity, and (3) marked accumulation of malate and fumarate, which could inhibit PEP carboxylase activity (Owttrim and Colman, 1986). Metabolic flux analysis performed by Young et al (2011) suggested that PEP carboxylase and malic enzyme cooperate in Synechocystis sp. PCC 6803 (i.e.…”
Section: Effects Of Addition Of Metabolites On the Dcyabrb2 Mutant Unmentioning
confidence: 99%
“…Chlorophyll (Chl) fluorescence, which is sensitive to environmental changes and stress conditions that induce alterations in photosynthetic components (Iwai et al, 2008), can monitor the efficiency of linear electron flow (Baker et al, 2007) and has indicated that in N. oceanica (Simionato et al, 2013) and other algae, including C. reinhardtii (Berges et al, 1996;Li et al, 2010;Blaby et al, 2013), photosynthetic efficiency falls after N deprivation. Photosynthetically driven metabolic fluxes can also be probed by supplying 13 C-labeled bicarbonate/CO 2 and quantifying 13 C incorporation into metabolite pools (Shastri and Morgan, 2007;Feng et al, 2010;Young et al, 2011).…”
mentioning
confidence: 99%
“…As a first step, modeling will be required at the level of the metabolites themselves and is most probably best supported by the analysis of kinetic labeling data (Arita, 2003;Huege et al, 2007;Young et al, 2011). Collected experimental data may be (1) at metabolic steady state and isotopic steady state, (2) at metabolic steady state but not at isotopic steady state, or (3) at neither metabolic nor isotopic steady state.…”
mentioning
confidence: 99%
“…Dynamic metabolite changes have also been modeled in groundbreaking work on the primary metabolism in E. coli (Yuan et al, 2009). Mathematical methods are also now available to extract information from non-steady-state labeling kinetics and have been applied in studies of plant secondary metabolism (Heinzle et al, 2007) and photosynthesis (Young et al, 2011). The use of stable isotopes to analyze flux is likely to go hand in hand with the further development of mathematical models to extract information from non-steady-state labeling kinetics.…”
mentioning
confidence: 99%